Libertarian Municipalism, or on the Greatness of the Civil Society - Sepczyńska, Dorota (Res Publica. Revista de Historia de las Ideas Políticas, 2016)
The paper is an attempt to critically read and interpret political thought of the creator of libertarian municipalism. At the same time it is a research study on a variant of contemporary socialistic libertarianism. Besides the paper shows that there is a type of socialism today that doesn’t run away from realistic world, doesn’t hide in the sphere of abstractive advisements and doesn’t bind common good-being with the existence of the state. Murray Bookchin is one of those seldom thinkers who not only proclaim normative applause to the civil society but also make a true contribution to the analysis of its institutional sphere, people’s motivation regarding associational freedom and requirements of system’s change. Bookchin simply shows the idea of citizenship in an attractive way.